Robotic renal and adrenal oncologic surgery: A contemporary review - Kulthe Ramesh Seetharam Bhat; Marcio Covas Moschovas; Fikret Fatih Onol; Travis Rogers; Shannon Roof; Vipul R. Patel; Oscar Schatloff (Asian Journal of Urology)
Robot-assisted surgery has evolved over time. Radical nephrectomy with inferior vena cava thrombectomy is feasible and safe for level I, II and III thrombus in high volume centers. Though it is feasible for level IV thrombus, this procedure needs a multi-departmental co-operation. However, the safety of robot-assisted procedures in this subset is still unknown. Robot-assisted partial nephrectomy has been universally approved and found oncologically safe. Robotic adrenalectomy has been increasingly utilized for select cases, especially in bilateral tumors and for retroperitoneal adrenalectomy.